2020
DOI: 10.3390/atmos11040375
|View full text |Cite
|
Sign up to set email alerts
|

Halocarbon Emissions from Hazardous Waste Landfills: Analysis of Sources and Risks

Abstract: Landfills are sources of fugitive volatile organic carbon (VOC) emissions, including halocarbons. The objective of this study was to evaluate the contribution of halogenated VOCs to the health risks associated with the exposure of workers operating in landfills, gathering information on the role of endogenous/exogenous sources present in anthropized areas. A hazardous waste landfill located in Turin, Italy was used as a case study. Ambient concentrations of 10 pollutants (BTEX, styrene, 1,3,5-trimethylbenzene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The investigated organic compounds are highly volatile compounds that produce negative effects on human health and contribute to the greenhouse effect. Monitoring and limiting the presence of these substances in the atmosphere is thus crucial, in particular where different types of emission sources are present [ 73 ]. On the other hand, studies have reported various chronic and subchronic effects from exposure to heavy metals [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The investigated organic compounds are highly volatile compounds that produce negative effects on human health and contribute to the greenhouse effect. Monitoring and limiting the presence of these substances in the atmosphere is thus crucial, in particular where different types of emission sources are present [ 73 ]. On the other hand, studies have reported various chronic and subchronic effects from exposure to heavy metals [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Possible associations between certain types of cancer such as for liver cancer, kidney cancer, pancreatic cancer, and non-Hodgkin's lymphomas and living close to garbage disposal sites/land lls have been studied yet the evidence is inconsistent. 37,38,39 In addition most of the studies on this subject looked the association between living close to garbage disposal sites/land lls and risk of cancer in adults (and not in children). 40 The nding of this study children living in garbage disposal areas/land lls are at higher odds of developing cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Both HIAs and HRAs are well-known topics among the scientific community. Decades of toxicological, clinical, and epidemiological research support the tools and methodologies currently applied [4,5]. Several modelling tools have been developed in support of HIA and HRA studies.…”
Section: Introductionmentioning
confidence: 99%